Seasonal variation of coarse aerosol particle concentration at Syowa Station, Antarctica - Kazuo Osada; Masahiko Hayashi; Keiichiro Hara; Masanori Yabuki; Makoto Wada; Masataka Shiobara; Takashi Yamanouchi; Kouji Fujita (National Institute of Polar Research, 2010)
Number-size distributions (D_p>0.3 μm) of atmospheric aerosol particles were measured at Syowa Station, Antarctica, from February 2004 to January 2006. Volume concentrations of coarse particles (D_p 1.0-5.0 μm) were low in December to January and high in the rest of the year. To identify factors controlling the seasonal variation of coarse particle concentrations at Syowa Station, seasonal variations of wind speed distribution over the Southern Ocean, sea ice extent, wind speed at the edge of sea ice and at Syowa Station, and seasonal patterns of backward air trajectories were compared with the volume concentrations of coarse particles. Patterns of backward air trajectories and changes in size distributions of coarse particles associated with sea ice extent suggest changes in major source areas of sea salt particles observed at Syowa Station: coastal areas near Syowa in February and March, but far north of the sea ice edge, around 60゜ south, in October.